1973
DOI: 10.1177/000348947308200620
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotological Significance of Alterations of Pursuit Eye Movements and the Pendular Eye Tracking Test

Abstract: Smooth pursuit eye movements can be studied if the patient follows a target that moves horizontally in a pendular way. The eye movements can be recorded with electrooculographic technique, and the tracings obtained studied for abnormalities. This constitutes the Pendular Eye Trackin Test (PETT). Three different deformations of PETT tracings have been observed: 1) a %asically normal shaped curve with superimposed fast movements; 2 ) a deformed curve and 3) an absence of the normal sinusoidal tracing. In disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…The average saccade was 2.5° (SD = 0.5), presumably large enough to be observed by the naked eye. However, in contrast to the previous findings, several authors have reported tracking at 30°/sec or more with few or no sizable saccades (11,73,74). …”
contrasting
confidence: 88%
“…The average saccade was 2.5° (SD = 0.5), presumably large enough to be observed by the naked eye. However, in contrast to the previous findings, several authors have reported tracking at 30°/sec or more with few or no sizable saccades (11,73,74). …”
contrasting
confidence: 88%
“…[3]; (6) a search for positioning nystagmus as de scribed by Dix and Hallpike [4]; (7) a search for cervical nystagmus as described by Greiner et al [7]; (8) a search for vertebro-basilar deprivation nys tagmus as described by Caussc ct al. [2]; (9) a bithermal caloric test according to Freyss et al [5j; directional preponderance and canal paresis were manually calculated, resulting in a computation of the total number of beats during the culmination; results were compared with the normal range for each laboratory;…”
Section: Methodsmentioning
confidence: 99%
“…Also Corvera [6], Norrden [5] and Lhneda [12] used the sinusoidal wave in their examina tions. On the other hand Baloh et al [7], Schalen [9], Schalen et al [10], Yamazaki [13] and Tamada et al [14] utilized triangu lar target waves.…”
Section: Target Wave O F Smooth Pursuitmentioning
confidence: 99%
“…The slow eye movement is one of the principal subsystems in the oculomo tor system together with the fast eye move ment (e.g. saccadic eye movement) [2][3][4], Clinical reports of smooth pursuit of patients with neurological disorders were reported by Jung and Kornhuber [4], Norrden [5] and Corvera [6], However, their analyses were based on qualitative evaluation using the ENG recording paper. Quantitative analysis of smooth pursuit has been tried by Baloh et al [7], Mizukoshi et al [8], Schalen [9] and Schalen et al [10], In most of these reports, the triangular wave or velocity ramp were utilized as target movements.…”
Section: Introductionmentioning
confidence: 99%